The inclusive learning center book : for preschool children with special needs - Isbell, Christy; Isbell, Rebecca (Silver Spring (Md.) : Gryphon House, 2005)
"A resource book for preschool teachers, containing information for creating an inclusive learning center classroom and adaptable activities for children with varying special needs"--Provided by publisher.
Lisäpainokset: Repr. 2010.
Includes bibliographical references and index.
Keywords: Inclusive education -- United States; Classroom learning centers -- United States. -- Planning; Children with disabilities -- Education (Preschool) -- United States; erityiskasvatus; inkluusio; vammaiset; lapset (ikäryhmät); opetus; erityisopetus; varhaiskasvatus; Yhdysvallat